Health data and global power inequalities: challenging the world data order - Nick Couldry; Ulises Ali Mejías (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2020)
Today's global media infrastructures involve not just media, but the continual extraction and circulation of data across digital platforms, with health data being an important data domain. The extraction and use of health data raises particular human rights issues. This paper reviews, fist, the basic risks to individuals from unconstrained collection, use and transfer of their personal health data; second, the implications of the fast-growing health data sector for social power generally; and third, the wider implications if current trends related to commercial exploitation of personal health data are not interrupted. A new global debate is needed to address these trends and their basis in a highly unequal political economy which benefis the same countries that profied from historical colonialism. We articulate here - in new ways - the challenges addressed by the 1980 MacBride Report, but for a very differently confiured world.